STRENGTHENING INDONESIA'S EIT LAW TO COMBAT RANSOMWARE THREATS: A LEGAL FRAMEWORK ANALYSIS - Alpajri, Muhammad; Effendi, Erdianto; Rahmadan, Davit (Jurnal Ilmiah Advokasi, 2025)
Ransomware is a type of malware designed to lock or encrypt victim data so that it cannot be accessed. Once the victim's data is locked, the perpetrator will ask for a ransom to restore access, usually in the form of digital currency such as Bitcoin which is difficult to track. Ransomware crimes are regulated in Article 33 of the ITE Law, however, Article 33 of the Electronic Information and Transactions Law (UU ITE) has weaknesses in its formulation because it does not include specific elements related to ransomware crimes, especially in relation to the element of requesting ransom payments. This creates a lack of legal certainty regarding ransomware crimes so that many cases of ransomware crimes cannot be prosecuted due to legal gaps. The purpose of this study is to provide input to law enforcement, police, prosecutors, judges, and the community and government in Countering the Threat of Ransomware Crimes in Indonesia. Based on the results of the study and discussion, it can be concluded. First, Article 33 of the Electronic Information and Transactions Law only regulates disruption of electronic systems, but does not explicitly include the elements of "extortion" or "demand for ransom payment" which are the core of ransomware crimes. Second, to strengthen the Electronic Information and Transactions Law and Indonesia's legal framework in countering the threat of ransomware, several important steps must be taken. First, one of the main solutions in dealing with ransomware crimes is to add provisions that explicitly regulate this crime in legislation, especially in the Electronic Information and Transactions Law. Keywords: Information and Electronic Transactions Law, Ransomware Crime, Indonesia